P300 Event-Related Potentials Differentiate Better Performing Individuals With Traumatic Brain Injury: A Preliminary Study of Semantic Processing. Issue 4 (July 2017) - Davis, Tara M.; Hill, Benjamin D.; Evans, Kelli J.; Tiffin, Shelby; Stanley, Nicholas; Fields, Kelly; Russ, Katherine; Bindele, Huybrechts Frazier; Gordon-Hickey, Susan
Abstract : Objective: To measure the effect of traumatic brain injury on the cognitive processing of words, as measured by the P300, in a semantic categorization task. Participants: Eight adults with a history of moderate to severe traumatic brain injury and 8 age- and gender-matched controls. Design: A pilot study measuring cognitive event-related potentials in response to word pairs that were either in same or different semantic categories. Main Measures: The P300 (P3b) component of the auditory event-related potential and neuropsychological assessment. Results: Two patterns of P300 amplitude related to brain injury were observed. Participants with poorer performance on neuropsychological tests exhibited reduced P300 amplitude as compared to controls but showed the typical P300 parietal scalp distribution. In contrast, better performing participants demonstrated robust P300 amplitude but a substantially altered scalp distribution, characterized by the recruitment of anterior brain regions in addition to parietal activation. Conclusions: The recruitment of frontal areas after traumatic brain injury may represent compensatory neural mechanisms utilized to successfully maximize task performance. The P300 in a semantic processing paradigm may be a sensitive marker of neural plasticity that could be used to improve functional outcomes in cognitive remediation paradigms. Abstract : Supplemental Digital Content is Available in the Text.